(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Tony F, Soemarno, Wiadnya DGR, Hakim L. 2020. Diversity of reef fish in Halang Melingkau Island, South Kalimantan, Indonesia. Biodiversitas 21: 4804-4812. Reef fish is one benchmark to determine a coral reef ecosystem’s biodiversity. Reef fish communities are important in coral reef ecosystems because of their trophic relationships with other biotic components. The aim of this study was to determine the biodiversity of reef fish on Halang Melingkau Island, Kotabaru District, South Kalimantan, Indonesia. This research was conducted in March-August 2019. Coral reef fish data were collected using an underwater visual census method. Transects were applied as close as possible to the substrate using a 50 m roll-up measuring tape. Three transects were applied at each station. A total of 98 reef fish species from 19 families were recorded in this study. The fish community in Halang Melingkau island belongs to the family of Pomacentridae, Labridae, Chaetodontidae, Scaridae, Haemulidae, Lutjanidae, Scolopsidae, Serranidae, Caesionidae, Holocentridae, Siganidae, Pomacanthidae, Apogonidae, Pempheridae, Scorpaenidae, Tetraodontidae, Blenniidae, Platacidae, and Zanclidae. The highest abundance of reef fish was 1.88 ind/m2, and the lowest was 0.14 ind/m2. The dominance index (C) ranged from 0.03 to 0.13, the homogeneity index (E’) ranged from 0.72 and 0.94, and the diversity index (H’) ranged from 2.17 to 3.53. Water quality data measurements of temperature, brightness, current speed, pH, and DO (Dissolved Oxygen) were within the tolerance limits of water quality standards based on the Minister of Environment Decree No. 51 of 2004, Republic of Indonesia.